2016
DOI: 10.5144/0256-4947.2016.409
|View full text |Cite
|
Sign up to set email alerts
|

Retinal nerve fiber layer thickness in a healthy Turkish population measured by optical coherence tomography

Abstract: BACKGROUNDNormative optical coherence tomography (OCT) data is required for different subsets of the population as ethnic differences in retinal nerve fiber layer (RNFL) thickness have been reported. An OCT database for the normal Turkish population is not commercially available.OBJECTIVESQuantify peripapillary RNFL thickness in a Turkish population.DESIGNCross-sectional, descriptive study.SETTINGNumune Training and Research Hospital, Adana, Turkey.SUBJECTS AND METHODSRNFL measurements performed by Spectral OC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
(25 reference statements)
0
2
1
Order By: Relevance
“…In our research, a relationship between age of participants, AxL, and RNFL was detected, but it was not statistically significant. Compared to the investigation of M. Cubuk et al, no statistically significant correlations were also found between age and RNFL in ophthalmologically healthy adults [28]. In our study, we observed that FD% values in the C 1 , C 2.5 , and R 1.5 sectors were similar between the 3 × 3-mm and 6 × 6-mm scans.…”
Section: Discussioncontrasting
confidence: 84%
“…In our research, a relationship between age of participants, AxL, and RNFL was detected, but it was not statistically significant. Compared to the investigation of M. Cubuk et al, no statistically significant correlations were also found between age and RNFL in ophthalmologically healthy adults [28]. In our study, we observed that FD% values in the C 1 , C 2.5 , and R 1.5 sectors were similar between the 3 × 3-mm and 6 × 6-mm scans.…”
Section: Discussioncontrasting
confidence: 84%
“…It is known that structural damage be ahead of visual field loss detected by standard perimetry. So quantitative analysis of RNFL and ONH is more reliable way of glaucoma assessment [ 11 ]. Ishkawa et al measured macular sub layer thickness and showed that macular ganglion cell complex was thinner in eyes with perimetric glaucoma [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A normal OCT database is required for different subsets of the population, which can vary depending upon racial or ethnic differences. 19 However, no normal OCT database is commercially available for the Turkish population. Thus, we aimed to describe the normative database of PPAA in Caucasian Turkish population aged between 18 and 80 years.…”
Section: Discussionmentioning
confidence: 99%